Changes of milk-specific IgE and serum total IgE in infants with eczema induced by milk allergen - Ge QIAN; Wu GUO; Dengting WU; Linfei LI (Pifu-xingbing zhenliaoxue zazhi, 2021)
Objective: To study the changes of milk-specific IgE and total serum IgE in infants with severe eczema induced by milk allergy at the different ages. Methods: Totally 57 infants with severe eczema induced by milk allergy were recruited. Both milk-specific IgE and serum IgE were measured, and the degrees of lesion severity were assessed at the beginning and end of the study. The study period was 30 months. Participants were required to avoid milk consumption during the investigation. Results: Among 57 patients, the average SCORAD score at the end of the observation was significantly lower than that at the beginning of the observation (6.17±5.03 vs 56.98±10.24, t=29.08, P<0.01). The value of milk-specific IgE at the end of the observation was significantly lower than that at the beginning of the observation [(2.05±1.70) kU/L vs (16.50±9.87) kU/L, t=11.04, P<0.01]. The multiples of the value of serum IgE at the end of the observation was significantly lower than that at the beginning of the observation [(4.50±1.08) times vs (11.99±5.35) times, t=10.51, P<0.01]. Conclusion: The symptoms of patients with severe eczema induced by milk allergy can alleviate after the long period of milk avoidance with decreasing levels of milk-specific IgE and serum IgE.